Induction of apoptosis and oxidative stress in estrogen receptor-negative breast cancer, MDA-MB231 cells, by ethanolic mango seed extract - Abdullah, Al-Shwyeh Hussah (BMC Complement Altern Med, 2015)
BACKGROUND: In this study, the effect of mango kernel extract in the induction of apoptosis of the breast cancer (MDA-MB-231) cell line was examined. This is an attempt to discover alternatives to current therapeutic regimes in the treatment of breast cancers. METHODS: The pro-apoptotic markers, Bax, cytochrome c, caspases-. -8 and −9, and anti-apoptotic markers, Bcl-2, p53 and glutathione were determined in MDA-MB231 cells treated for 12 and 24 h with mango kernel extract. RESULTS: The results showed that the extract produced a time- and dose-dependent increases in pro-apoptotic proteins and oxidative stress markers with a corresponding decrease in anti-apoptotic markers. CONCLUSIONS: Based on the findings, mango kernel extract modulates redox balance in MDA-MB-231 breast cancer cells with a tendency for apoptotic cell death. The changes observed in this study may collectively underlie the basis for the cell death induced in MDA-MB-231 breast cancer cells by mango kernel extract. Thus, mango kernel extract has potential to be developed into an antibreast cancer mixture, and hence these results are worth studying further.